Diagn Interv Radiol 2022
DOI: 10.5152/dir.2022.21460
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion tensor imaging and diffusion-weighted imaging on axillary lymph node status in breast cancer patients

Abstract: This article will examine the usefulness of diffusion tensor imaging (DTI) and diffusion-weighted imaging (DWI) on the assessment of axillary lymph nodes (ALN) of breast cancer patients. METHODSAxillary lymph nodes in 66 breast cancer patients were examined by DTI and DWI, and the largest lymph node with increased cortical thickness in axilla was selected. Morphological features, apparent diffusion coefficient (ADC), volume anisotropy, and fractional anisotropy values were measured by using a special software.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Previous studies have evaluated the characteristics of SLN or ALN status in BC using conventional MRI and radiomics features ( 12 , 26 ), diffusion imaging with different postprocessing models ( 10 - 12 , 27 ), and artificial neural networks ( 28 ). However, to the best of our knowledge, few studies have reported on the clinical value of syMRI coupled with conventional and diffusion-weighted MRI in predicting SLNs metastases for patients with BC.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have evaluated the characteristics of SLN or ALN status in BC using conventional MRI and radiomics features ( 12 , 26 ), diffusion imaging with different postprocessing models ( 10 - 12 , 27 ), and artificial neural networks ( 28 ). However, to the best of our knowledge, few studies have reported on the clinical value of syMRI coupled with conventional and diffusion-weighted MRI in predicting SLNs metastases for patients with BC.…”
Section: Discussionmentioning
confidence: 99%
“…The other two studies also added the application of diffusion-weighted imaging (DWI) sequences into their procedures. There are increasing developments in the usage of ADC that add value to the diagnosis 47 and localization of breast cancer 48 , 49 and breast DWI as an essential part of a multiparametric breast MRI is welcome by the European Society of Breast Radiology. 50 Dietzel et al 51 found that DWI can be used as a substitute for the delayed phase in DCE-MRI, shortening the scanning time without losing diagnostic information.…”
Section: Application Of Mri-rfa In Breast Cancer Therapymentioning
confidence: 99%